The effect of systemic administration of desmopressin on cochlear function in guinea pigs. (July 2013) - Chihara, Yasuhiro; Wong, Christopher; Curthoys, Ian S.; Brown, Daniel J.
Abstract Conclusions: Systemic desmopressin (dDAVP) administration in guinea pigs for up to 2 weeks induced only minor or no significant changes in cochlear sensitivity, suggesting that other factors may be required to induce the cochlear dysfunction that is usually associated with endolymphatic hydrops. Objectives: To investigate the effects of chronic systemic administration of dDAVP, a synthetic analog of vasopressin, on cochlear sensitivity in guinea pigs. Methods: dDAVP was administered subcutaneously via a mini-osmotic pump, at a rate of 0.2 ng/kg/min (low-dose group) or 2.0 ng/kg/min (high-dose group) for up to 2 weeks. Cochlear responses (compound action potentials) and distortion product otoacoustic emissions (DPOAEs) were measured. Example specimens were scanned using X-ray micro-tomography (micro-CT). Results: Compared with the control group, the low-dose dDAVP group showed a significant threshold increase in response to a 2 kHz tone-burst after 2 weeks of treatment, and also a decrease in the amplitude of the DPOAE after 1 week of treatment. However, individual results were variable and the high-dose dDAVP group showed no significant change compared to the control group. In the micro-CT images, two of four ears in the low-dose group showed mild hydrops, but no hydrops was found in the three ears sampled from the high-dose group.